Time budget pressure, moral intensity and dysfunctional audit behavior among audit trainees. - Ismail, Hashanah; Muhamed, Salmah (2012)
This paper examines incidence of dysfunctional audit behavior (DAB) amongst Accounting undergraduate students who have just undergone a six months industrial attachment with an audit firm as part of the graduation requirement under Halatuju 2. Results based on 106 responses show a low correlation between DAB and time budget pressure but a significant relationship between DAB and moral intensity with types of firms for industrial training. Students who underwent industrial training with the Big 4 appear to have higher moral intensity and engage less in DAB acts. Results suggest that exposure to an Ethics course could mitigate propensity to engage in DAB. Additionally a factor to consider is that students’ oral communication apprehension could contribute to incidence of DAB among audit trainees.